STUDI PENGEMBANGAN EKONOMI KERAKYATAN DI KAWASAN WISATA JAWA TIMUR MELALUI PENGUATAN KELEMBAGAAN SOSIAL EKONOMI MASYARAKAT LOKAL - Ashar, Khusnul; Fitanto, Bahtiar; Supartono, - (Journal of Indonesian Applied Economics, 2009)
East  Java Province  is one of  the  Indonesia  region which high  in poverty  rate,even higher than national average. One of the effective model  to alleviate povertyimplemented in developing countries is the model that able to integrate the poor intothe tourism sector (Ashley, 2000; Cattarinich, 2001). General aim of this study is tobuild a proper institution which able to enlarge an opportunities to the poor to be-come an integral part of the tourism sector. Specific aim of this first year study are:to describe the tourism economic structure in research area of Batu; to describe therelationship intensity   between tourism industry and the local economy; to identifythe capacity of economic resources of the poor households in term of education level,skills, and capital accessibility; and to identify the social capital and the existenceand the nature of local institutions. Analysis unit of this study are : the tourism busi-ness unit,  the tourists; and the poor household.  This study found that : The tourismsector has significance role in the economic structure of Batu. The relationship be-tween tourism industry and local economy is high. Man power, local fruits and veg-etable are the main production input for the tourism businesses. Education level ofthe poor household members is not so low. However, for high level positions in mod-ern tourists industry  was mostly filled by people from other area. The role of formaleconomic institutions such as banks and cooperative business unit in study are notsignificant for the poor. In order to gain additional capital, the poor mostly rely onthe traditional capital accumulation revolving system (Arisan). Beside Arisan, socialcapital of the poor is also accumulated trough social and religious gathering.Keywords: tourism, local institution